The (Un)canniness in Identities Among Biracial Taiwanese-Vietnamese Students - Chi Hong Nguyen (SAGE Open)
The identities of Taiwanese-Vietnamese students’ academic and social lives are not well-informed in the current body of research on international students in Vietnam, plus identities are often reported to be dynamic. Aiming to bridge this gap and add nuance to understanding dynamism in identities, this study explores the sense-making of these biracial students’ identities. The concepts of canniness and uncanniness in Heidegger’s phenomenology and interpretivism were used to unpack the fluidity of identities as ambiguous. In-depth interviews were conducted with 18 Taiwanese-Vietnamese students studying at nine universities in the Mekong Delta of Vietnam, offspring of the major Vietnamese bride-sending location during the 2000s. This study revealed that these biracial students hold an intersection of Taiwanese national, Taiwanese racial, and Vietnamese ethnic identities. This intersection makes them feel uncanny when they encounter ambivalence in racial, ethnic, and national identities that creates the ambiguity of their identities in legal status and social interactions. This study raises and calls for debates over a new term in the findings: quasi-international students—those with ambiguous and ambivalent racial, ethnic, and national identities—as the point of departure for future research on international student mobility and international education. Because Heidegger’s phenomenology centers around individuals’ sense-making of social processes, it is suggested that future studies focus on the influences of societal and cultural structures on biracial students’ ambiguous identities.